A Managerial Leadership Model for Teacher Performance Improvement: Insights from Madrasah Aliyah in Garut Regency - Dayum Sugandi; R. Supyan Sauri (Journal of General Education and Humanities, 2026)
Madrasah principals' managerial leadership is crucial for enhancing teacher performance, a key factor in the quality of Madrasah Aliyah education. This study examines principals' managerial leadership practices to improve teacher performance, focusing on work discipline, academic supervision, and instructional planning. To address challenges such as inconsistent performance and discipline at Madrasah Aliyah Al Maarif and Al Ulfa in Garut Regency, this study uses a descriptive qualitative case study design. Data from interviews, observations, and documents were analysed using reduction, display, and verification, with triangulation to ensure validity. Findings show principals' leadership boosts performance through structured planning, organisation, implementation, and evaluation. Planning goes beyond administration, with principals as motivators and models. Organisation involves systematic learning management, professional development, democratic styles, and collaborative environments. Implementation leverages motivation, communication, and supportive settings to advance professionalism through guidance, supervision, and training. Evaluation provides direction, communication, and potential nurturing through monitoring and appraisals. Ultimately, effective leadership holistically integrates these functions with discipline, supervision, and planning to elevate teacher professionalism and educational quality.